Acceptance towards automated vehicles in urban traffic: A survey of pedestrian’s attitudes and behavioral intentions - Kevin A. Harkin; A. Marie Harkin; Katharina Kummerer; Madlen Ringhand; Tibor Petzoldt (Transportation Research Interdisciplinary Perspectives)
Acceptance is vital for the successful integration of automated vehicles (AVs) into urban traffic. This is not only true for potential users of such vehicles. Other road users’ perceptions and actions are just as important when designing AVs. Previous research has primarily focused on pedestrians’ direct interactions with AVs (e.g., willingness to cross). However, there are other ways in which pedestrians might react to the presence of AVs. In the worst case, they avoid participating in urban traffic or obstruct AVs. To address this issue, this study surveyed N = 1,995 residents of Munich, Germany, to assess their perceptions of the potential integration of AVs and their expected behavior in urban traffic. The survey was structured around four dimensions: direct interactions with AVs (Pedestrian-AV Interaction), perceptions of the general future behavior of AVs towards pedestrians (Traffic Climate), the broader impact on urban traffic (Societal Factors) and Demographic and Individual Factors. Acceptance was measured by general attitudes toward AVs in urban traffic and their intention to cross, avoid and sabotage AVs. The results showed that attitudes and behavioral intentions could be accurately predicted across these four dimensions, except for sabotage intentions. Expectations regarding direct interactions with AVs emerged as the most important aspect, although perceptions of the general future behavior of AVs and broader impacts on urban traffic also influenced behavioral intentions and attitudes. The findings underscore the importance of exploring pedestrian acceptance beyond mere willingness to cross to ensure a comprehensive understanding of pedestrian attitudes toward AVs in urban traffic.